A Simplified Modeling Method of UVMS Dynamics Based on Quasi-Lagrange Equation - Qingyu YANG; Ping REN; Hao WANG (水下无人系统学报, 2024)
As a kind of complex system with strong nonlinearity, strong coupling, time variance, redundancy, and high dimension, the modeling, motion control, and stability analysis of an underwater vehicle-manipulator system(UVMS) are very challenging. In dynamics modeling, the traditional Lagrange equation is often used to model the complex UVMS with high degrees of freedom, which requires the operation of derivation and partial derivation of the generalized coordinates and their derivatives and will face the problems of a large amount of calculation and low modeling efficiency. Therefore, this paper proposed a simplified dynamics modeling method for UVMS with 6+n degree-of-freedom based on the quasi-Lagrange equation, which could reduce the amount of calculation in the symbolic formula derivation and improve the modeling efficiency and the accuracy of the results. Finally, the numerical simulation of a UVMS model was carried out with the physical parameters of the underwater vehicle BlueROV and the underwater manipulator Reach Alpha, and the simulation results verified the complex coupling of the UVMS. The dynamics model based on the proposed method had a clear equation form, which not only provided strong support for the study of control algorithms and the optimization of coupling forces but also a basis for the design of dynamics parameters and the study of trajectory planning.